LEGAL PROTECTION ISSUE IN THE MINORITY RELIGION OF THE NON-GREATEST SIX - Karni, Asrori S. (Faculty of Law Universitas Panca Bhakti, 2019)
Adherents of minority religions outside the greatest six religions was still had to face the uncertainty from the state in religious rights service and legal protection. It was started from the right to obtain permission to build a synogogue, religious education rights, marriage registration, birth certificate, put the religion identity in official document column, and so on. The fundamental problem was a flurry of religious recognition concept by the state. There were some opportunities for short and long term breakthrough solutions need to be explored.